On Higher Regularized Traces of a Differential Operator with Bounded Operator Coefficient Given in a Finite Interval - Sezer, Yonca; Baksi, Ozlem; Karayel, Serpil (SPRINGER BASEL AG, 2021)
In this work, we find a higher regularized trace formula for a regular Sturm-Liouville differential operator with operator coefficient.
Keywords: Hilbert space; Eigenvalue; spectrum; trace class operator; regularized trace; 47A10; 34L20; 34L05; Mathematics